(untitled) (MiKAN, 2012)
It is, perhaps, not too extravagant to suggest that in the history of western thought there are three great explorations of the philosophy of love, Plato’s, Augustine’s, and Freud’s. If, for the former two, sex is either the gateway or the obstacle to love (which remains to be seen), for the latter, love is the mystification of sex (or one possible such a one). In this essay, I hope to explore the proposition that all love in the West from Plato into the Christianity and Judaism of late antiquity is Platonic love. The goal, as in so much of my work, is to thoroughly displace the notion of the natural in human behavior, insisting on its absolute, fundamental queerness.